2015
DOI: 10.1136/bjsports-2015-094723
|View full text |Cite
|
Sign up to set email alerts
|

Proximal muscle rehabilitation is effective for patellofemoral pain: a systematic review with meta-analysis

Abstract: BackgroundProximal muscle rehabilitation is commonly prescribed to address muscle strength and function deficits in individuals with patellofemoral pain (PFP). This review (1) evaluates the efficacy of proximal musculature rehabilitation for patients with PFP; (2) compares the efficacy of various rehabilitation protocols; and (3) identifies potential biomechanical mechanisms of effect in order to optimise outcomes from proximal rehabilitation in this problematic patient group.MethodsWeb of Knowledge, CINAHL, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 46 publications
3
95
0
4
Order By: Relevance
“…Longer duration of pain and worse symptoms and function, measured at baseline, remain predictors of poor PFP prognosis up to 8 years later. Education of health practitioners and the general public is recommended, to change the long-held belief that PFP is self-limiting and to improve treatment outcomes 53 54What are the new findings?

A substantial proportion (>50%) of people with patellofemoral pain (PFP) who responded at follow-up still have notable symptoms 5–8 years after a 6-week programme of treatment and education.

The large majority of people with PFP at follow-up did not have signs of radiographic knee osteoarthritis, which does not support the proposition that long-term PFP is associated with structural patellofemoral osteoarthritis changes in younger adults.

How might it impact on clinical practice in the near future?

Medical professionals need to educate patients that PFP is not always self-limiting, especially those with long PFP duration (>12 months) and worse symptoms and function.

…”
Section: Discussionmentioning
confidence: 99%
“…Longer duration of pain and worse symptoms and function, measured at baseline, remain predictors of poor PFP prognosis up to 8 years later. Education of health practitioners and the general public is recommended, to change the long-held belief that PFP is self-limiting and to improve treatment outcomes 53 54What are the new findings?

A substantial proportion (>50%) of people with patellofemoral pain (PFP) who responded at follow-up still have notable symptoms 5–8 years after a 6-week programme of treatment and education.

The large majority of people with PFP at follow-up did not have signs of radiographic knee osteoarthritis, which does not support the proposition that long-term PFP is associated with structural patellofemoral osteoarthritis changes in younger adults.

How might it impact on clinical practice in the near future?

Medical professionals need to educate patients that PFP is not always self-limiting, especially those with long PFP duration (>12 months) and worse symptoms and function.

…”
Section: Discussionmentioning
confidence: 99%
“…This mal-tracking leads to reduced patellofemoral joint contact area which increases the load on that joint and, hence, pain (Powers et al 2017). Consequently, many treatments for patellofemoral pain have focused on improving patellofemoral control, through, for example, proximal (hip abductors and quadriceps) strengthening and stretching exercises (Lack et al 2015), patella mobilisations (Rowlands and Brantingham 1999), patella taping (Barton et al 2015). Both hypomobility and hypermobility of the patella are considered to be clinically important.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we have shown that BF running increases the activation of GMax during stance phase, a muscle involved in hip extension and stabilization. With evidence that proximal lower-limb muscle exercise can have rehabilitative value for persons with patellofemoral pain [18], BF running could be a potential training or recovery solution for these individuals.…”
Section: Conclusion ▼mentioning
confidence: 99%